Rates of chronic absenteeism in Montessori and non-Montessori Title 1 schools - LeBoeuf, Lee; Goldstein-Greenwood, Jacob; Lillard, Angeline S. (Frontiers in Education, 2023)
In this study, we asked whether Montessori schools, which tend to have high student engagement, are associated with lower average rates of chronic absenteeism and/or smaller racial disparities therein relative to non-Montessori schools. Using data from the Civil Rights Data Collection, we identified a sample of Title 1 Montessori and non-Montessori schools with propensity score matching, and we used multilevel modeling to compare racial disparities in chronic absenteeism rates across school types. There was no significant difference in the average overall rates of chronic absenteeism across school types; nor were there sizable or significant differences in average racial disparities in the rates of chronic absenteeism between Black and White or Hispanic and White students, though Montessori schools had slightly lower average rates for White students. We discuss how shortcomings in the way chronic absenteeism data are collected limit intervention work by preventing researchers from answering questions about why students are chronically absent.